(untitled) (Global Journal of Human-Social Science, 2018)
This research work investigates the activities of the Niger Delta militants and how it affects the developmental strides of the Nigerian economy. We use primary data with a target population of students, oil company workers, civil servants, public servants, farmers, and entrepreneurs in Bayelsa State being the main hob of militancy and very rich in oil production than any other state. Tables were constructed to show the level of responses and their percentages. In the end, Chi-Square was used to test the relationship between militancy and the economy. The results revealed that militancy has a strong significant effect on crude oil production/supply as well as the Nigerian economy. Militancy in the Niger Delta Region has led to the loss of revenue accruable to the Federal Government of Nigeria. The activities of militants in the Niger Delta Region have significantly affected business life, create unemployment and devastated human lives in the Niger Delta region. Militancy also supports illegal bunkering.